Leveraging Behavioral Science to Increase the Impact of Economic Inclusion Programming - Datta, Saugato; Joshi, Mukta; MacLeod, Catherine; Zini, Michele Davide (Washington, DC: World Bank, 2022)
Behavioral science-the study of how humans make decisions and take actions—can provide insight into a host of issues that impact the effectiveness of programs that rely on people acting in certain ways. Behavioral science can be utilized to understand how living in poverty, with chronically scarce resources, affects people's decisions and actions. This can be particularly effective when combined with other program components in economic inclusion programs, which offer a bundle of coordinated, multidimensional interventions that support individuals, households, and communities in their efforts to increase their incomes and assets. By incorporating an understanding of behavioral science into economic inclusion programming, governments and nongovernment organizations seeking to bring millions out of poverty with limited resources can ensure that their programs are designed to account for human behavior.